2010
DOI: 10.1051/limn/2010005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and controls of nitrogen stable isotopes of particulate organic matter in subtropical lakes

Abstract: -Nitrogen stable isotope composition (d 15 N) of particulate organic matter (POM) has been used to infer dominant nitrogen cycling processes in lakes. However, very few studies have compared the isotope variations in lakes along trophic state and other biogeochemical gradients. Here we report an analysis of d 15 N POM and selected environmental variables from 96 subtropical lakes to assess the patterns and controls of isotope variations. Results indicate that d 15 N POM values varied from x 2.8 to 13.2‰ and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There are different δ 15 N compositions in rivers, lakes, reservoirs and marine regions, because of characteristic living organisms and inanimate matter. Many studies have suggested that variations in δ 15 N PN and δ 15 N TDN are associated with thermal and hydrological characteristics, trophic states, nitrogen sources, N 2 fixation, and phytoplankton abundance (Altabet, 2006; Gu et al, 2006, Gu, 2009; Gu and Schelske, 2010; Hou et al, 2013). However, the key factors that control variations in δ 15 N PN and δ 15 N TDN are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…There are different δ 15 N compositions in rivers, lakes, reservoirs and marine regions, because of characteristic living organisms and inanimate matter. Many studies have suggested that variations in δ 15 N PN and δ 15 N TDN are associated with thermal and hydrological characteristics, trophic states, nitrogen sources, N 2 fixation, and phytoplankton abundance (Altabet, 2006; Gu et al, 2006, Gu, 2009; Gu and Schelske, 2010; Hou et al, 2013). However, the key factors that control variations in δ 15 N PN and δ 15 N TDN are not well understood.…”
Section: Introductionmentioning
confidence: 99%